Assessment of the cell biovolume of phytoplankton widespread in coastal and inland water bodies. (1st November 2016) - Napiórkowska-Krzebietke, Agnieszka; Kobos, Justyna
Abstract: The biovolume of phytoplankton must be assessed accurately in order to identify the ecological status of water bodies in line with the WFD requirements. Hence, the current study has been carried out to verify and improve the precision of as well as to facilitate and accelerate estimations of phytoplankton biovolume by reviewing and rearranging the basic geometrical shapes of these organisms applied in such evaluations. The latest standards comprise 17 geometric shapes and equations suitable for estimations of cell/filament/colony biovolume and additionally include taxa-specific 'geometric correction factors' to fit real shapes and 'hidden dimension factors' to achieve data on hardly measureable dimensions. This paper also discusses possible obstacles to making correct biovolume assessments, especially when analyzing taxa of special concern, e.g. Ceratium hirundinella, C . furcoides or Pediastrum duplex and Pseudopediastrum boryanum . Our comparison of two approaches, the previous and the new one, revealed that they yield statistically significantly different biovolume results of these species. Some recommendations how to deal with the new and old methods of biovolume estimations and how to reduce the possibility of errors with overestimation and underestimation were also given. The more recent method can be said to give more precise estimates of phytoplankton biovolume. Besides, it facilitates more rapid phytoplankton analyses in most cases, which is very useful when assessing the ecological status of lakes during routine monitoring programs. Graphical abstract: Highlights: The latest DIN EN standards comprise 17 geometric shapes. Hidden dimension factors were used to achieve data on hardly measureable dimensions. Taxa-specific geometric correction factors to fit real shapes were recommended. Difficulties in making correct biovolume assessments were discussed.